Influence of MURDER Strategy to Improve Students' Understanding of Islamic Religious Education Subjects - Emi Lilawati; Dian Kusuma Wardani; Yudithia Adi Wicansa (SCHOOLAR: Social and Literature Study in Education, 2021)
This study aims to determine the influence of MURDER learning strategy with daily replay of grade XI students at SMK Islam Al-Qomar. The type of research used is quasy experiment. The population in this study was all students of grade XI SMK Islam Al-Qomar Nganjuk. The technique used for sampling is Random Sampling. The sample of this study was grade XI MM students as experimental class and XI TKR as control class. The research instrument in this study is a Daily Deuteronomy test consisting of 20 Multiple Choice Questions and the results to see differences in students' comprehension skills in PAI material from control classes and experimental classes. The data obtained was analyzed using t sample independent test. Based on the findings of the study, it was concluded that there were differences in students' comprehension skills between experimental and control classes, and the results showed that in classes taught using MURDER strategies were more effective than unedentative classes using MURDER strategies